Synthesis of ZnO nanoparticles from electric arc furnace dust - Bui A.-H.; Le D.-C.; Nguyen T.-T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper presents a hydrometallurgical treatment of electric arc furnace (EAF) dust taken from a Vietnamese steelmaking plant to obtain zinc oxide (ZnO) nanoparticles by using aqueous ammonium carbonate solution as a leaching agent. Characterization of the EAF dust was conducted by XRD technique, SEM observation, and manual wet chemical analysis. The results showed that total zinc (Zn) of the dust was 42.69 wt.% and existed mainly in the forms of zincite - ZnO, simonkolleite - Zn5(OH)8Cl2H2O, and franklinite - ZnFe2O4. The leached condition, in which the ammoniac carbonate concentration was 300 g/l and the time was 90 minutes, was found to provide the highest leaching efficiency of 85.29 % when the temperature was fixed at 60 oC and the ratio of solid/liquid was 1/6. After some steps of the subsequent treatment, the ZnO nanoparticles with the purity of 99.5 % and the size of 100 nm were obtained from thermal decomposition of zinc carbonate hydroxide - Zn5(CO3)2(OH)6.